Long-Term Monitoring of Amphibian Populations of a National Park in Northern Spain Reveals Negative Persisting Effects of Ranavirus, but Not Batrachochytrium dendrobatidis - Bosch, Jaime; Mora-Cabello de Alba, Amparo; Marquínez, Susana; Price, Stephen J.; Thumsová, Barbora; Bielby, Jon (Frontiers in Veterinary Science, 2021)
Amphibians are the most highly threatened vertebrates, and emerging pathogens are a serious threat to their conservation. Amphibian chytrid fungi and the viruses of the Ranavirus genus are causing disease outbreaks worldwide, including in protected areas such as National Parks. However, we lack information about their effect over amphibian populations in the long-term, and sometimes these mortality episodes are considered as transient events without serious consequences over longer time-spans. Here, we relate the occurrence of both pathogens with the population trends of 24 amphibian populations at 15 sites across a national Park in northern Spain over a 14-year period. Just one out 24 populations presents a positive population trend being free of both pathogens, while seven populations exposed to one or two pathogens experienced strong declines during the study period. The rest of the study populations (16) remain stable, and these tend to be of species that are not susceptible to the pathogen present or are free of pathogens. Our study is consistent with infectious diseases playing an important role in dictating amphibian population trends and emphasizes the need to adopt measures to control these pathogens in nature. We highlight that sites housing species carrying Ranavirus seems to have experienced more severe population-level effects compared to those with the amphibian chytrid fungus, and that Ranaviruses could be just as, or more important, as other more high-profile amphibian emerging pathogens.